Molecular and immunological analysis of a polymorphic periplasmic protein of Borrelia burgdorferi. - Simpson, W J (1991)
Borrelia burgdorferi is the causative agent of Lyme disease, a tick-borne spirochetosis with a worldwide prevalence. To assist the categorization and typing of fresh isolates from global foci, we have identified a unique species-specific periplasmic protein (P22-A) conserved among all North American and European isolates examined. The gene encoding this antigen was cloned, and the recombinant was used to screen serum collected from experimentally infected animals. Although antibodies were detected in all infected animals at 21 days after inoculation with live, low-passage spirochetes, the response was stronger in other animals that were inoculated with inactivated and lysed bacteria. This result, along with the immune electron microscopy data, suggests P22-A is concentrated in the periplasmic space. The P22-A antigens exhibited size heterogeneity among different isolates, ranging between 20 and 23 kDa, but as a group the P22-A antigens appeared to retain antigenic homogeneity. Thus, P22-A can serve as a structural marker for characterizing new isolates of B. burgdorferi and may prove useful in future serological assays with a mixture of B. burgdorferi-specific antigens.